A new class of high performance metal-fiber thermoplastic composites for additive manufacturing. (June 2023) - Mohanty, Debapriya Pinaki; Arnold, Brian J.; Baruah, Sweta; Chandrasekar, Srinivasan; Mann, James B.
Abstract: The performance of a new class of metal fiber reinforced polymer (FRP) produced by additive manufacturing (AM) is discussed and compared with a commercially available polyethylene terephthalate glycol-PETG/carbon fiber composite. Aluminum alloy micro-fibers (Al6061-T6) produced by Modulation-Assisted Machining (MAM) are dispersed in a thermoplastic PETG matrix by screw extrusion. The filaments are feedstock for AM processing and sample preparation by fused deposition modeling (FDM). Mechanical testing, micro-hardness and wear testing protocols were used to evaluate the performance of the new FRP. The PETG/Al FRP composite samples show performance advantages over samples printed from commercially available PETG/carbon fiber filament. Computerized tomography (CT) and scanning electron microscopy (SEM) are used to explore the characteristics and distribution of the aluminum micro-fiber in the composite and the fracture surfaces in the test samples. AM processing with these new metal fiber/matrix formats enabled by MAM has unique potential to access high-performance composites applications.